2015
DOI: 10.3311/ppci.7608
|View full text |Cite
|
Sign up to set email alerts
|

Air Void Distribution of Asphalts Determined by Computed Tomography

Abstract: Durability and functionality of hot mix asphalts (HMA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The pores content and their distribution were determined alongside the sample using CT method, by measuring the pores with size larger than 0.01 mm. This method provides high accuracy and could be used as an alternative method for the other standard laboratory tests [29]. Figs.…”
Section: Computed Tomography Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pores content and their distribution were determined alongside the sample using CT method, by measuring the pores with size larger than 0.01 mm. This method provides high accuracy and could be used as an alternative method for the other standard laboratory tests [29]. Figs.…”
Section: Computed Tomography Resultsmentioning
confidence: 99%
“…The examination of permeability, pores, and pore size distribution of HCP is feasible using CT method [29]. Siemens Somatom 16 was used for the CT tests at the Diagnostic and Oncoradiology Institute of Kaposvar University in Hungary.…”
Section: Computed Tomographymentioning
confidence: 99%
“…With regard to the air void content derived from CT measurements and obtained using the EN 12697-8 standardised method, it can be concluded that there is a need for further research, in which not only a logical correlation but also a mathematical conversion should be established. In the latter case the nominal aggregate size must be taken into account [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, cyclic loading to determine the ratio of modulus in wet to dry conditions was used to determine the specimen's moisture sensitivity. Moreover, since the Durability and functionality of hot mix asphalts (HMA) depend on air voids and their characteristics [27], in this research the laboratory specimens were prepared in 7 ± 1 % of the air voids.…”
Section: Laboratory Programmentioning
confidence: 99%